Towards the improvement of policy and strategy development for the sustainable management of non-timber forest products: Swaziland: A case study - Dlamini, Cliff Sibusiso (Stellenbosch : University of Stellenbosch, 2007)
Thesis (PhD (Forest and Wood Science))—University of Stellenbosch, 2007.